Roughness characterization of well-polished surfaces by measurements of light scattering distribution - Zhenrong, Zheng; Jing, Zhou; Peifu, Gu (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
According to vector scattering and scalar scattering theory, the relationship of BRDF (bidirectional reflectance distribution function) of light scattering from micro-rough surface with TIS (total integrated scattering) is analyzed. Roughness statistical characterization such as RMS (root mean square), PSD (power spectral density) function are deduced by TIS of polished surface. Based on the light scattering measurement theory, an automatic measure system of light scattering with one dimensional scanning method is built, BRDF of two kinds of polished surfaces (silica surface and Ag reflector) have been measured. PSD of two surfaces has been given by light scattering measurements, roughness characterization of two surfaces has been compared with the data tested by profile meter. The results show that the light scattering measurement method has great application prospects as regards nondestructive measurement for polishing surfaces.
Optica Applicata, Vol. 40, 2010, nr 4, s. 811-818
Keywords: optyka; light scattering; roughness; bidirectional reflectance distribution function (BRDF)